Orbital neuroblastoma metastasis: A case report and literature review - Yang, Wan-Ju (Medicine (Baltimore), 2019)
RATIONALE: Neuroblastoma is one of the most common tumors found in children, and mostly arises in the adrenal gland and paravertebral regions. Orbital neuroblastoma metastasis is relatively rare, and is associated with poor prognosis. Since the symptoms and signs of orbital neuroblastoma are not specific, its diagnosis remains challenging. PATIENT CONCERNS: A 3-year-old girl presented with periorbital ecchymoses (raccoon eyes) and proptosis for 40 days. DIAGNOSES: Abdominal magnetic resonance imaging (MRI) and sonography analysis revealed a large mass in the left adrenal gland (primary tumor). The computed tomography and MRI further revealed multiple soft tissue masses in the skull and both orbits with erosion of the adjacent bones (the metastasis). The histological analysis of the tumor removed from the right orbit confirmed the diagnosis of neuroblastoma. INTERVENTIONS: The mass on the right face was surgically removed. OUTCOMES: The patient exhibited no deteriorative signs at the 6-month follow-up. LESSONS: Clinical manifestations, such as periorbital ecchymoses and proptosis, in combination with radiological analysis and histological findings, are important for the diagnosis of orbital neuroblastoma metastasis.